Operasi Chondrolaryngoplasty dalam Perspektif Fikih Islam: Chondrolaryngoplasty Surgery in the Perspective of Islamic Fiqh - Rosmita, Rosmita; Santi Sarni; Nur Anita (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
This study aims to determine the nature of chondrolaryngoplasty surgery and to determine the perspective of Islamic jurisprudence on chondrolaryngoplasty surgery. The research method used is descriptive qualitative, namely library research and using normative, perspective, phenomenological and health approaches. This study found that: first, Chondrolaryngoplasty is a type of plastic surgery to change the shape of body organs with surgical methods and is a type of surgery performed on the larynx or throat to change the shape and size of the laryngeal cartilage, the effect of chondrolaryngoplasty surgery is to produce a more feminine or masculine angle on the neck. Second, the law of chondrolaryngoplasty surgery in Islamic jurisprudence is haram when this procedure is carried out only for aesthetic purposes, namely to beautify or beautify and change the creation of Allah Swt., but there are exceptions when this surgery is darurīyyāt then the law becomes mubah. However, cases like this are still rare. As for the implications of this study, it is expected that someone who will undergo a chondrolaryngoplasty surgery procedure must first know and study the law of this surgery, so as not to fall into sin, namely changing the creation of Allah Swt., and individuals who want to undergo chondrolaryngoplasty surgery must first consult a specialist doctor in this field, to minimize side effects after undergoing chondrolaryngoplasty surgery.